Peran Self-efficacy dan Internship Experience terhadap Job Readiness melalui Work Interest pada Mahasiswa Tingkat Akhir - Anggraini Putri Widyastuti; Hertiana Ikasari; Diana Aqmala; Awanis Linati Haziroh (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the effect of work experience and Self-efficacy on work readiness with Work Interest as a mediating variable among final-year students of the Faculty of Economics and Business, Dian Nuswantoro University. This study uses a quantitative approach with a causal associative design. Data were obtained through a closed-ended questionnaire using a five-point Likert scale distributed to 112 respondents according to multivariate sampling criteria, then analyzed using SEM-PLS through SmartPLS 4.1.1.6. The results revealed that Self- efficacy and work experience had a positive and significant effect on Work Interest, with Mastery experience and culture as the dominant indicators. Work Interest was also found to increase Job Readiness, particularly through aspiration, while internship experience had a direct effect through relevance. Conversely, Self- efficacy had no direct effect on Job Readiness because the confidence indicator was relatively weak. However, Work Interest was found to be a significant mediator between Self- efficacy and work experience with Job Readiness, confirming the important role of Work Interest in increasing the Job Readiness of final-year students.